Personalized peptide vaccines for cancer therapy: current progress and state of the art. Issue 6 (2nd November 2017) - Wada, Satoshi; Yada, Erica; Ohtake, Junya; Sasada, Tetsuro
ABSTRACT: Introduction : Accumulating evidence for the feasibility and efficacy of cancer immunotherapy is ushering in a paradigm shift for cancer treatment. Notably, immune checkpoint inhibitors, such as antibodies against cytotoxic T-lymphocyte-associated antigen-4 and programmed cell death-1/programmed cell death ligand 1, show substantial clinical benefits in certain types of cancers. Nevertheless, the response rates to immune checkpoint inhibitors are only 20–30% of patients at most, possibly because the activated immune response is not sufficiently specific. The activation of non-tumor-specific cells leads, theoretically, to autoimmunity and not to tumor regression. Therefore, other approaches that can activate tumor-specific immune cells, such as cancer peptide vaccines, must be developed to improve cancer immunotherapeutic options. Areas covered : In this review, the authors discuss current and future perspectives on cancer-specific immunotherapies, particularly cancer peptide vaccines. Expert commentary : Personalized peptide vaccines against peptides that are recognized by patient T cells elicit immediate, tumor-specific immune responses. Furthermore, advances in genomics and bioinformatics have facilitated the generation of personalized peptide vaccines derived from neo-antigens, which have proven safe in clinical trials. In the future, combination therapies that utilize checkpoint inhibitors and peptide vaccines may improve response rates and patient outcomes.